2019
DOI: 10.3390/nu11102393
|View full text |Cite
|
Sign up to set email alerts
|

Food Components and Dietary Habits: Keys for a Healthy Gut Microbiota Composition

Abstract: The gut microbiota is a changing ecosystem, containing trillions of bacteria, continuously shaped by many factors, such as dietary habits, seasonality, lifestyle, stress, antibiotics use, or diseases. A healthy host–microorganisms balance must be respected in order to optimally maintain the intestinal barrier and immune system functions and, consequently, prevent disease development. In the past several decades, the adoption of modern dietary habits has become a growing health concern, as it is strongly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
414
1
30

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(450 citation statements)
references
References 172 publications
(216 reference statements)
5
414
1
30
Order By: Relevance
“…In this short-term dietary intervention study in elderly obese women (EO), we showed that two weeks of balanced Mediterranean diet with mild caloric deficit, as a part of a metabolic-nutritional-psychological rehabilitation program, improved the patients' metabolic picture, and that such an improvement was accompanied by the recovery of a balanced health-promoting configuration of the gut microbiota. The Mediterranean diet is indeed considered the optimal strategy to prevent microbiota dysbiosis and protect intestinal permeability [55]. In line with the literature available on gut microbiota and metabolic disorders [36][37][38][39][40][41], the intestinal microbiota of EO subjects, as compared to non-obese elders (EC) living in the same territory (i.e., Italy), showed several dysbiotic features, including: (i) a tendency to reduced biodiversity (generally recognized as a hallmark of a healthy gut); (ii) decreased relative abundance of health-promoting, SCFA producers (mainly belonging to the Lachnospiraceae and Ruminococcaceae families, i.e., Lachnospira, Blautia, Coprococcus, Roseburia, Ruminococcus and Oscillospira) as well as Parabacteroides; and (iii) increased proportions of subdominant taxa, such as Collinsella and Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…In this short-term dietary intervention study in elderly obese women (EO), we showed that two weeks of balanced Mediterranean diet with mild caloric deficit, as a part of a metabolic-nutritional-psychological rehabilitation program, improved the patients' metabolic picture, and that such an improvement was accompanied by the recovery of a balanced health-promoting configuration of the gut microbiota. The Mediterranean diet is indeed considered the optimal strategy to prevent microbiota dysbiosis and protect intestinal permeability [55]. In line with the literature available on gut microbiota and metabolic disorders [36][37][38][39][40][41], the intestinal microbiota of EO subjects, as compared to non-obese elders (EC) living in the same territory (i.e., Italy), showed several dysbiotic features, including: (i) a tendency to reduced biodiversity (generally recognized as a hallmark of a healthy gut); (ii) decreased relative abundance of health-promoting, SCFA producers (mainly belonging to the Lachnospiraceae and Ruminococcaceae families, i.e., Lachnospira, Blautia, Coprococcus, Roseburia, Ruminococcus and Oscillospira) as well as Parabacteroides; and (iii) increased proportions of subdominant taxa, such as Collinsella and Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of gut microbiota is influenced not only by lifestyle (i.e., dietary pattern, smoking, and exercise) but also by maternal transfer, age, and antibiotic use. Dietary composition, an element of lifestyle, has a direct and profound effect on gut bacteria [131]. The Western diet (high fat/high sugar) reduces the diversity of gut microbiota in mice, resulting in an increase in Bacteroides species and Ruminococcus torques [132].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Moreover, changing barrier function and nutrient requirements (with age) may influence skeletal muscle composition and function [101]. It has been reported that diet and exercise can modify the composition and diversity of gut microbiota [102][103][104] and may thus provide a practical means for enhancing gut and systemic immune functioning.…”
Section: Gut Microbiota and Probioticsmentioning
confidence: 99%